Divalent cation competition with [3H]saxitoxin binding to tetrodotoxin- resistant and -sensitive sodium channels. A two-site structural model of ion/toxin interaction (The Rockefeller University Press, 1993)
Monovalent and divalent cations competitively displace tetrodotoxin and saxitoxin (STX) from their binding sites on nerve and skeletal muscle Na channels. Recent studies of cloned cardiac (toxin-resistant) and brain (toxin-sensitive) Na channels suggest important structural differences in their toxin and divalent cation binding sites. We used a partially purified preparation of sheep cardiac Na channels to compare monovalent and divalent cation competition and pH dependence of binding of [3H]STX between these toxin-resistant channels and toxin-sensitive channels in membranes prepared from rat brain. The effects of several chemical modifiers of amino acid groups were also compared. Toxin competition curves for Na+ in heart and Cd2+ in brain yielded similar KD values to measurements of equilibrium binding curves. The monovalent cation sequence for effectiveness of [3H]STX competition is the same for cardiac and brain Na channels, with similar KI values for each ion and slopes of -1. The effectiveness sequence corresponds to unhydrated ion radii. For seven divalent cations tested (Ca2+, Mg2+, Mn2+, Co2+, Ni2+, Cd2+, and Zn2+) the sequence for [3H]STX competition was also similar. However, whereas all ions displaced [3H]STX from cardiac Na channels at lower concentrations, Cd2+ and Zn2+ did so at much lower concentrations. In addition, and by way of explication, the divalent ion competition curves for both brain and cardiac channels (except for Cd2+ and Zn2+ in heart and Zn2+ in brain) had slopes of less than -1, consistent with more than one interaction site. Two-site curves had statistically better fits than one-site curves. The derived values of KI for the higher affinity sites were similar between the channel types, but the lower affinity KI's were larger for heart. On the other hand, the slopes of competition curves for Cd2+ and Zn2+ were close to - 1, as if the cardiac Na channel had one dominant site of interaction or more than one site with similar values for KI. pH titration of [3H]STX binding to cardiac channels showed a pKa of 5.5 and a slope of 0.6-0.9, compared with a pKa of 5.1 and slope of 1 for brain channels. Tetramethyloxonium (TMO) treatment abolished [3H]STX binding to cardiac and brain channels and STX protected channels, but the TMO effect was less dramatic for cardiac channels. Trinitrobenzene sulfonate preferentially abolished [3H]STX binding to brain channels by action at an STX protected site.(ABSTRACT TRUNCATED AT 400 WORDS)